2020
DOI: 10.1001/jamaoto.2020.3053
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Efficacy of a Povidone-Iodine Nasal Antiseptic for Rapid Inactivation of SARS-CoV-2

Abstract: IMPORTANCE Research is needed to demonstrate the efficacy of nasal povidone-iodine (PVP-I) against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). OBJECTIVE To evaluate the in vitro efficacy of PVP-I nasal antiseptic for the inactivation of SARS-CoV-2 at clinically significant contact times of 15 and 30 seconds. INTERVENTIONS The SARS-CoV-2, USA-WA1/2020 strain, virus stock was tested against nasal antiseptic solutions consisting of aqueous PVP-I as the sole active ingredient. Povidone-iodine was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 32 publications
(64 reference statements)
4
70
0
1
Order By: Relevance
“…The ratio for ACE2 was five-fold greater in the nose than in the distal respiratory tract [40]. Other repurposing treatments as a nasal antiseptic have been tested in vitro, such as Povidone-Iodine, which has shown activity against SARS-CoV-2 [48]. In the present study, we showed the in vitro therapeutic potential of BromAc against SARS-CoV-2 with a threshold efficient dose at 100 µg/20 mg/mL.…”
Section: Discussionsupporting
confidence: 47%
“…The ratio for ACE2 was five-fold greater in the nose than in the distal respiratory tract [40]. Other repurposing treatments as a nasal antiseptic have been tested in vitro, such as Povidone-Iodine, which has shown activity against SARS-CoV-2 [48]. In the present study, we showed the in vitro therapeutic potential of BromAc against SARS-CoV-2 with a threshold efficient dose at 100 µg/20 mg/mL.…”
Section: Discussionsupporting
confidence: 47%
“…However, this approach has major limitations including patient experience of using povidone iodine in the nose, allergic potential, and thyroid disease concerns. Povidone Iodine can become ineffective when diluting from available commercial 5% or 10% solutions and can be effective only up to 4 hours post application 25 . NE-BZK has an added advantage that safety has been previously demonstrated in humans through two different phase 1 clinical trials using the same nanoemulsion technology with a similar cationic surfactant.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24] Aqueous intranasal preparations of PVI-I at concentrations as low as 0.5% completely inactivated SARS-CoV-2 with contact times as short as 15 seconds, compared to 70% ethanol, which demonstrated only partial viral inactivation. 20,23 A 0.45% Betadine throat spray was similarly efficacious following a 30-second contact time. 21 A prior study using MERS-CoV and SARS-CoV showed viral inactivation with a PVP-I mouthwash concentration as low as 0.23% after 15 seconds.…”
Section: Virucidal Activitymentioning
confidence: 99%
“…Although in vivo efficacy of PVP‐I against SARS‐CoV‐2 remains unknown, several in vitro studies have demonstrated promising virucidal activity 20–24 . Aqueous intranasal preparations of PVI‐I at concentrations as low as 0.5% completely inactivated SARS‐CoV‐2 with contact times as short as 15 seconds, compared to 70% ethanol, which demonstrated only partial viral inactivation 20,23 . A 0.45% Betadine throat spray was similarly efficacious following a 30‐second contact time 21 .…”
Section: Povidone‐iodinementioning
confidence: 99%
See 1 more Smart Citation